2022
DOI: 10.1159/000525831
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights and Novel Approaches toward Individualized Arteriovenous Fistula Care

Abstract: The aim of the paper is to summarize the current understanding of the molecular biology of arteriovenous fistula (AVF). It intends to encourage vascular access teams, care providers, and scientists, to explore new molecular tools for assessing the suitability of patients for AVF as vascular access for maintenance hemodialysis (HD). This review also highlights most recent discoveries and may serve as a guide to explore biomarkers and technologies for the assessment of kidney disease patients choosing to start k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…systematic review and meta-analysis comprising thirteen studies with a combined population of 1,512 subjects, 48 biomarkers were assessed and no significant association between any of the assessed routine circulating biomarkers and AVF failure was observed (Morton et al 2016) (Wang et al 2022). Previous studies have shown that the ESRD patients had a higher level of serum CHI3L1 (Tatar et al 2017) compared to the healthy controls.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…systematic review and meta-analysis comprising thirteen studies with a combined population of 1,512 subjects, 48 biomarkers were assessed and no significant association between any of the assessed routine circulating biomarkers and AVF failure was observed (Morton et al 2016) (Wang et al 2022). Previous studies have shown that the ESRD patients had a higher level of serum CHI3L1 (Tatar et al 2017) compared to the healthy controls.…”
Section: Accepted Manuscriptmentioning
confidence: 99%